A Crossover Comparison of Standard and Telerobotic Approaches to Prenatal Sonography. (24th April 2018) - Adams, Scott J.; Burbridge, Brent E.; Badea, Andreea; Kanigan, Nadine; Bustamante, Luis; Babyn, Paul; Mendez, Ivar
Abstract : Objectives: To determine the feasibility of a telerobotic approach to remotely perform prenatal sonographic examinations. Methods: Thirty participants were prospectively recruited. Participants underwent a limited examination (assessing biometry, placental location, and amniotic fluid; n = 20) or a detailed examination (biometry, placental location, amniotic fluid, and fetal anatomic survey; n = 10) performed with a conventional ultrasound system. This examination was followed by an equivalent examination performed with a telerobotic ultrasound system, which enabled sonographers to remotely control all ultrasound settings and fine movements of the ultrasound transducer from a distance. Telerobotic images were read independently from conventional images. Results: The mean gestational age ± SD of the 30 participants was 22.9 ± 5.3 weeks. Paired‐sample t tests showed no statistically significant difference between conventional and telerobotic measurements of fetal head circumference, biparietal diameter, or single deepest vertical pocket of amniotic fluid; however, a small but statistically significant difference was observed in measurements of abdominal circumference and femur length ( P < .05). Intraclass correlations showed excellent agreement (>0.90) between telerobotic and conventional measurements of all 4 biometric parameters. Of 21 fetal structures included in the anatomic survey, 80% of the structures attempted across all patients were sufficiently visualized by the telerobotic system (range, 57%–100% per patient). Ninety‐seven percent of patients strongly or somewhat agreed that they would be willing to have another telerobotic examination in the future. Conclusions: A telerobotic approach is feasible for remotely performing prenatal sonographic examinations. Telerobotic sonography (robotic telesonography) may allow for the development of satellite ultrasound clinics in rural, remote, or low‐volume communities, thereby increasing access to prenatal imaging in underserved communities.